PENGARUH PENDIDIKAN AGAMA DALAM KELUARGA TERHADAP AKHLAK REMAJA - admin, admin; Maryani, Yani; syah, Herman; Fikruzzaman, Daden (THORIQOTUNA: Jurnal Pendidikan Islam, 2021)
This study aims to determine the effect of Religious Education in the Family on Adolescent Morals in RW 03 Kampung Cidoyang, Sukakerta Village, Panumbangan District, Ciamis Regency. By using Religious Education in the Family can increase Adolescent Morals. The method used in this study is a descriptive method with a quantitative approach that is research in the form of revealing current conditions by considering past conditions through processing the figures obtained in the study. Based on the results of data processing, the results show that the influence of Religious Education in the Family on Adolescent Morals in RW 03 in Cidoyang Village, Sukakerta Village, Panumbangan Sub-District, Ciamis District has a significant influence with a high category of tcount = 6.1685 > t table = 1,67469. Religious Education in the Family affects Adolescent Morals by 42.25% while the remaining 57.75% is thought to be influenced by other factors, such as playing environmental factors and internal factors such as mind and mental, development of feelings, social considerations and moral development. Ased on the results of this study, it can be concluded that adolescent morals can increase through Religious Education in the Family. It is recommended that in shaping adolescent morals, parents should be able to motivate their teenage children to have good morals in their daily lives and instill Faith Education in the Family with various methods so that adolescent morals improve.